Analises de mutações e de seus efeitos na expressão do gene SRY em casos de disgenesia gonadal XY - Cunha Júnior, José Luiz Rosenberis (2010)
Orientadores: Maricilda Palandi de Mello, Celso Eduardo Benedetti, Fernanda Caroline Soardi